استیذان (اجازت لینے سے) متعلق شرعی حکمتیں اور آداب : The Shari‘ah Wisdoms and Etiquettes Related to Seeking Permission (Isti’dhān) (Khairulummah, 2025)
Islam is a religion of nature, therefore it gives complete protection to the private life of man. It is aware of the natural needs of man, therefore it has formulated such rules and high social values that if we apply them in our lives, we will find peace, comfort and happiness. Islam has complete guidance on living in houses, entering them, and all the matters that are done in them. It is believed that only a stranger should inform about entering a house, but Islamic teachings say that whether it is a stranger or a member of the house, he should fully respect the private life of the people living in the house. Yes, there are some stricter teachings for strangers and some leniency for those living in the house, but etiquette has been taught to everyone, the sole purpose of which is to avoid bitterness, complications, and disgrace and to form a society that is outwardly and inwardly pure. The article under consideration describes the religious etiquette before and after entering homes and other private places. Hopefully, the readers will benefit greatly from it.